Identification of Thermophilic Bacteria from Tirta Lebak Buana Hot Spring in Serang, Banten, Indonesia - Lischer, Kenny (UI Scholars Hub, 2021)
Since Taq polymerase was first explored and identified from thermophilic bacteria, these bacteria have become well-known sources of thermostable enzymes. New thermophilic bacteria have been investigated to broaden biodiversity and translation research. Studies have shown interests in Indonesia because of thermophilic bacteria found in hot springs. This country is traversed by the ring of fire and has more than 70 volcanoes, resulting in the wide distribution of hot springs across the country. Although many reports have been performed, studies have yet to explore thermophilic bacteria in Tirta Lebak Buana hot springs, Java Island, Indonesia. This research was the first to examine thermophilic bacteria in Tirta Lebak Buana hot spring. Two samples from two different sampling sites were obtained and analyzed through 16srRNA analysis (sampling sites A and B). Measurements indicated that the temperature (50 °C) in sampling site A was higher than that in sampling site B (40 °C), but they had similar pH (7.0). Polymerase chain reaction (PCR) showed that the 16srRNA of the specimen was around 1465 bp. The analysis of the 16srRNA sequence revealed that the obtained bacteria have a similar sequence and close relationship with Bacillus subtilis subsp. stercoris strain N12.